2022
DOI: 10.3390/ijms23052626
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Retinal TGFβ Signaling Aggravates Neurodegeneration by Modulating Pro-Apoptotic and MAP Kinase Pathways

Abstract: Transforming growth factor β (TGFβ) signaling has manifold functions such as regulation of cell growth, differentiation, migration, and apoptosis. Moreover, there is increasing evidence that it also acts in a neuroprotective manner. We recently showed that TGFβ receptor type 2 (Tgfbr2) is upregulated in retinal neurons and Müller cells during retinal degeneration. In this study we investigated if this upregulation of TGFβ signaling would have functional consequences in protecting retinal neurons. To this end, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In our study, we first demonstrated that Tgf-β could attenuate DNA damage and improve cell viability of UV-radiated 661W cells ( Figure 1 A–F), which is supported by previous studies [ 11 , 12 , 15 , 32 , 33 , 34 ]. The general neuroprotective role of Tgf-β against various harmful stimuli has been demonstrated [ 35 , 36 , 37 , 38 , 39 ]. In terms of the role of Tgf-β and photoreceptor damage in ocular diseases, a recent study showed that Tgf-β signaling is vital for photoreceptor viability, while deletion of Tgf-β signaling resulted in thinner outer nuclear layer and accelerated retinal degeneration [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we first demonstrated that Tgf-β could attenuate DNA damage and improve cell viability of UV-radiated 661W cells ( Figure 1 A–F), which is supported by previous studies [ 11 , 12 , 15 , 32 , 33 , 34 ]. The general neuroprotective role of Tgf-β against various harmful stimuli has been demonstrated [ 35 , 36 , 37 , 38 , 39 ]. In terms of the role of Tgf-β and photoreceptor damage in ocular diseases, a recent study showed that Tgf-β signaling is vital for photoreceptor viability, while deletion of Tgf-β signaling resulted in thinner outer nuclear layer and accelerated retinal degeneration [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The general neuroprotective role of Tgf-β against various harmful stimuli has been demonstrated [ 35 , 36 , 37 , 38 , 39 ]. In terms of the role of Tgf-β and photoreceptor damage in ocular diseases, a recent study showed that Tgf-β signaling is vital for photoreceptor viability, while deletion of Tgf-β signaling resulted in thinner outer nuclear layer and accelerated retinal degeneration [ 38 ]. More importantly, Tgf-β exerts its neuroprotective role through direct impact on photoreceptors [ 35 ], which is also consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the significantly increased levels of prototype galectin-1 (Drgal 1-L2) also play a role in retinal development and photoreceptor regeneration [ 209 ]. Transforming growth factor β (TGFβ) was injected in Müller cells as it is thought to have neuroprotective properties; mice with cell type-specific deletion of Tgfbr2 in retinal neurons and Müller cells (Tgfbr2ΔOC), in combination with a genetic model of photoreceptor degeneration (VPP), were used to analyze TGFβ signaling [ 210 ]. While retinal morphology was not altered from TGFβ signaling, the upregulation of the MAP kinase pathway and the activation of pro-apoptotic genes markedly accelerated VPP-induced photoreceptor degradation in mice (Tgfbr2OC; VPP) [ 210 ].…”
Section: Novel Therapeutic Targets In Preclinical Phase: Neuroprotect...mentioning
confidence: 99%
“…Transforming growth factor β (TGFβ) was injected in Müller cells as it is thought to have neuroprotective properties; mice with cell type-specific deletion of Tgfbr2 in retinal neurons and Müller cells (Tgfbr2ΔOC), in combination with a genetic model of photoreceptor degeneration (VPP), were used to analyze TGFβ signaling [ 210 ]. While retinal morphology was not altered from TGFβ signaling, the upregulation of the MAP kinase pathway and the activation of pro-apoptotic genes markedly accelerated VPP-induced photoreceptor degradation in mice (Tgfbr2OC; VPP) [ 210 ]. Due to this, TGFβ signaling in Müller cells and retinal neurons likely has a neuroprotective effect and may present novel therapeutic opportunities to halt photoreceptor deterioration [ 210 ].…”
Section: Novel Therapeutic Targets In Preclinical Phase: Neuroprotect...mentioning
confidence: 99%
“…It is also implicated in the pathogenesis of several diseases such as connective tissue diseases, skeletal diseases, fibrosis, and cancer progression ( Morikawa et al, 2016 ). They regulate the development and functions of the nervous system and their neuroprotective roles are increasingly recognized ( Dobolyi et al, 2012 ; Bielmeier et al, 2022 ; Lee et al, 2022 ). During the regenerative process of peripheral nerves, TGF-β is released by macrophages ( Sulaiman and Gordon, 2009 ), SCs ( Li et al, 2015 ; Clements et al, 2017 ), fibroblasts ( Clements et al, 2017 ), and the injured nerves ( van Rossum et al, 2008 ; Li et al, 2015 ) and is abundantly present in the nerve bridge microenvironment ( Xiao et al, 2014 ; Clements et al, 2017 ), implying its vital involvement in the process.…”
Section: Introductionmentioning
confidence: 99%